Pengaruh Internalisasi Budaya Disiplin Berbasis Nilai Islam dan Peran Wali Kelas terhadap Perilaku Santun Siswa SMPN 1 Kotagajah, Lampung Tengah - Az Zahra, Afifah Az Zahra; Gumilang, Ratih Gumilang; Muhammad Rifai; Muhammad Alfi Syahrin (Educational Research Center, 2026)
This study aims to analyze the influence of the internalization of Islamic values-based discipline culture and the role of homeroom teachers on the polite behavior of students at SMPN 1 Kotagajah, Central Lampung. The approach used is quantitative with a causal-associative survey design. The research sample consisted of 194 grade VIII students who were selected through probability sampling techniques. The results of multiple regression analysis showed that the discipline culture based on Islamic values and the role of homeroom teachers simultaneously had a significant effect on students' polite behavior, with the contribution of each variable to student polite behavior of 34%. These findings confirm that the internalization of Islamic values in the school discipline culture and the active role of homeroom teachers in character development have a positive impact on shaping students' polite behavior. This research is expected to contribute to the development of character education in public schools by effectively integrating religious values and the role of the supervisor.